Utilization of Coconut Shell Liquid Smoke on Quail Performance at Grower Period - R. M. Fadhila; N. Ulupi; H. Maheshwari (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Antioxidants from coconut shell liquid smoke can overcome oxidative stress in quail. This study aims to analyze the effect of coconut shell liquid smoke (ACTK) on the performance of quail (Coturnix coturnix japonica) during the grower period. The research method used a completely randomized designconsisting of 5 treatment levels with 3 replications, namely P0 (control), P1 (0.25 mL/L ACTK), P2 (0.50 mL/L ACTK), P3 (0.75 mL/L ACTK) and P4 (1 mL/L ACTK). Variables measured included initial body weight, final body weight, body weight gain, feed intake, water intake, feed conversion ratio (FCR),morbidity, mortality, and income over feed quail cost (IOFQC). The results showed that giving ACTK had no significant effect (P>0.05) on feed intake, water intake, and body weight gain. The morbidity and mortality rates in this study were 0%. The best FCR value was obtained at P4 (4.28). The highest IOFQC value was at P4 (Rp 1.578,92). This study concludes that giving coconut shell liquid smoke to female quails during the grower period through drinking water had no significant effect on feed intake, water intake, and body weight gain. A dose of 1 mL/L of ACTK produced the best FCR and IOFQC values.